PENGARUH PENERAPAN MODEL EXPERIENTIAL LEARNING (EL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Simanungkalit, Ferawati; Sinulingga, Karya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
His study aimed to determine the effect of the experiential learning model on students’ critical thinking skills in temperature and heat topics at grade XI of SMA Negeri 1 Laguboti. The study employed a quasi-experimental method using a pretest-posttest control group design. The sample consisted of two classes selected through simple random sampling, namely class XI-3 as the experimental group and class XI-2 as the control group. The research instrument was an essay test developed based on Facione’s critical thinking indicators. Data were analyzed using descriptive and inferential statistics, including normality, homogeneity, and t-test analyses. The results revealed that the mean score of critical thinking skills in the experimental class increased from 41.94 to 84.40 with an N-Gain of 0.73 (high category), while the control class increased from 41.67 to 76.23 with an N-Gain of 0.59 (moderate category). Hypothesis testing indicated that the experiential learning model had a significant effect on students’ critical thinking skills.